Contextual Emphasis in the Holy Quran and its Translation into English - Alsharou, Shaman (2016)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Shaman Alsharou entitled, "Contextual Emphasis in the Holy Quran and its Translation into English," submitted in November 2016. Thesis advisor is Dr. Basil A. Hatim. Soft and hard copy available.